Subcellular distribution of the soluble lytic transglycosylase in Escherichia coli. - Walderich, B (1991)
The localization of the major autolytic enzyme, the soluble lytic transglycosylase, in the different cell compartments of Escherichia coli was investigated by immunoelectron microscopy. Ultrathin sections were labeled with a specific antiserum against purified soluble lytic transglycosylase, and the antibody-enzyme complexes were visualized with colloidal protein A-gold. A preferential localization of the lytic transglycosylase in the envelope was observed, with only 20 to 30% of the enzyme left in the cytoplasm. Most of the enzyme associated with the cell wall was tightly bound to the murein sacculus. Sacculi prepared by boiling of cells in 4% sodium dodecyl sulfate could be immunolabeled with the specific antiserum, indicating a surprisingly strong interaction of the lytic transglycosylase with murein. The enzyme-substrate complex could be reconstituted in vitro by incubating pronase-treated, protein-free murein sacculi with purified lytic transglycosylase at 0 degrees C. Titration of sacculi with increasing amounts of enzyme indicated a limiting number of binding sites for about 1,000 molecules of enzyme per sacculus. Ruptured murein sacculi obtained after penicillin treatment revealed that the enzyme is exclusively bound to the outer surface of the sacculus. This finding is discussed in the light of recent evidence suggesting that the murein of E. coli might be a structure of more than one layer expanding by inside-to-outside growth of patches of murein.